MENGEMBALIKAN IDENTITAS MUARA ANGKE MELALUI STRATEGI PENGELOLAAN BUDIDAYA IKAN YANG BERKELANJUTAN - Wibin, Arlene; Jayanti, Theresia Budi (Jurusan Arsitektur dan Perencanaan, 2024)
Muara Angke, once a place rich in meaning and identity for fishermen, is facing a series of phenomena that have transformed it into a placeless place. Fishermen who once relied on the waters for their livelihoods now face significant challenges in finding sustenance from what they once called